a)14+3x=23
b)87=3x−6
c)3x+2=9
d)5x−6=4
e)4x−7=17
f)52=2x−6
g)3x+4=2
h)6−2x=2
i)5x−8=12
j)47=3x−4
k)4x+2=10
l)4−2x=−10
m)17+5x=32​



Odpowiedź :

Lea3

a)

[tex]14 + 3x = 23[/tex]

[tex]3x = 23 - 14[/tex]

[tex]3x = 9[/tex]

[tex]x = 9 \div 3 = 3[/tex]

b)

[tex]87 = 3x - 6[/tex]

[tex] - 3x = - 6 - 87[/tex]

[tex] - 3x = - 93[/tex]

[tex]x = ( - 93 )\div ( - 3) = 31[/tex]

c)

[tex]3x + 2 = 9[/tex]

[tex]3x = 9 - 2[/tex]

[tex]3x = 7[/tex]

[tex]x = 7 \div 3 = 2 \frac{1}{3} [/tex]

d)

[tex]5x - 6 = 4[/tex]

[tex]5x = 4 + 6[/tex]

[tex]5x = 10[/tex]

[tex]x = 10 \div 5 = 2[/tex]

e)

[tex]4x - 7 = 17[/tex]

[tex]4x = 7 + 17[/tex]

[tex]4x = 24[/tex]

[tex]x = 24 \div 4 = 6[/tex]

f)

[tex]52 = 2x - 6[/tex]

[tex] - 2x = - 6 - 52[/tex]

[tex] - 2x = - 58[/tex]

[tex]x = ( - 58) \div ( - 2) = 29[/tex]

g)

[tex]3x + 4 = 2[/tex]

[tex]3x = 2 - 4[/tex]

[tex]3x = - 2[/tex]

[tex]x = - \frac{2}{3} [/tex]

h)

[tex]6 - 2x = 2[/tex]

[tex] - 2x = 2 - 6[/tex]

[tex] - 2x = - 4[/tex]

[tex]x = ( - 4) \div ( - 2) = 2[/tex]

i)

[tex]5x - 8 = 12[/tex]

[tex]5x = 12 + 8[/tex]

[tex]5x = 20[/tex]

[tex]x = 20 \div 5 = 4[/tex]

j)

[tex]47 = 3x - 4[/tex]

[tex] - 3x = - 4 - 47[/tex]

[tex] - 3x = - 51[/tex]

[tex]x = ( - 51) \div ( - 3) = 17[/tex]

k)

[tex]4x + 2 = 10[/tex]

[tex]4x = 10 - 2[/tex]

[tex]4x = 8[/tex]

[tex]x = 8 \div 4 = 2[/tex]

l)

[tex]4 - 2x = - 10[/tex]

[tex] - 2x = - 10 - 4[/tex]

[tex] - 2x = - 14[/tex]

[tex]x = ( - 14) \div ( - 2) = 7[/tex]

m)

[tex]17 + 5x = 32[/tex]

[tex]5x = 32 - 17[/tex]

[tex]5x = 15[/tex]

[tex]x = 15 \div 5 = 3[/tex]

...............................
Zobacz obrazek Аноним